Evaluating e-Learning Resources - Riddy, Paul; Fill, Karen (Proceedings of the International Conference on Networked Learning, 2004)
MECA-ODL, an EU funded project, developed an evaluation methodology and online tool for assessing eLearning materials, modules and courses. This paper describes the MECA-ODL outcomes and compares them with a number of other schemes. The MECA-ODL approach embraces the complete lifecycle of an eLearning offering, from conception through development to delivery and evaluation. Formal reviews and hands-on workshops produced positive feedback, plus some suggestions for improvement. Informed by these and the reviews of other schemes, the paper proposes enhancements to the evaluation methodology and tool, which have potentially wider significance.